Broad-band high-energy emissions of the redback millisecond pulsar PSR J2129–0429. Issue 3 (23rd June 2018) - Kong, Albert K H; Takata, Jumpei; Hui, C Y; Zhao, J; Li, K L; Tam, P H T
ABSTRACT: We present the first results from a joint XMM-Newton and NuSTAR observation of the gamma-ray emitting millisecond pulsar compact binary PSR J2129–0429. X-ray emission up to about 40 keV is detected and the joint spectrum can be modelled with a power-law plus a neutron star atmosphere model. At a distance of 1.4 kpc, the 0.3–79 keV luminosity is 3.56 × 10 32 erg s −1 . We also detected a 0.64-d binary orbital period with a double-peaked structure across the wavebands. By combining the updated Fermi GeV data, we modelled the broad-band spectral energy distribution as well as the X-ray modulation with an intrabinary model involving shock interaction between pulsar wind and outflow from the companion star. Lastly, we report a high-resolution X-ray image provided by Chandra to rule out the proposed pulsar wind nebula associated with PSR J2129–0429.